Women empowerment and environmental sustainability in Africa - Elvis Dze Achuo; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2022)
This study examines the effect of women's socioeconomic empowerment on environmental sustainability in Africa over the 1996-2019 period. Results of the system Generalised Method of Moments (GMM) estimator reveal that women's socioeconomic empowerment is environment enhancing. Moreover, the findings reveal that the environmental impact of women's socioeconomic empowerment is modulated through GDP per capita and Foreign Direct Investments (FDI), leading to respective net effects of 0.002055 and 0.003478. These positive net effects are offset beyond respective threshold values of 9.513889 and 9.611398. These thresholds of GDP and FDI are critical for complementary policies relating to the link between women empowerment and environmental sustainability. Consequently, for women empowerment to effectively contribute to environmental sustainability in Africa, various governments, either through individual or concerted efforts should endeavour to create enabling business environments capable of attracting substantial FDI necessary to propel sustainable growth. Moreover, the nexus is not linear and hence, governments should also be aware of critical levels of FDI and GDP per capita at which, complementary policies are needed for women's socioeconomic empowerment to maintain a positive influence on environmental sustainability.
Keywords: B54; J16; O55; Q56; 330; Women empowerment; Environmental sustainability; Ecofeminism; Africa